Assembling a library of typical surgery video clips to construct a system for assessing the surgical difficulty of laparoscopic cholecystectomy. (28th January 2021) - Kurata, Masanao; Iwashita, Yukio; Ohyama, Tetsuji; Endo, Itaru; Hibi, Taizo; Umezawa, Akiko; Suzuki, Kenji; Watanabe, Manabu; Asai, Koji; Mori, Yasuhisa; Higashida, Masaharu; Kumamoto, Yusuke; et al.
Abstract: Background: To explore best practices for acute cholecystitis, it is necessary to construct a system to assess the difficulty of laparoscopic cholecystectomy (LC) based on intraoperative findings. In this study, multiple evaluators assessed videos of LC to assemble a library of typical video clips for 25 intraoperative findings. Methods: We have previously identified 25 items that contribute to surgical difficulty in LC. For each item, roughly 30‐second video clips were submitted from videos of LC performed at member institutions. We then selected one typical video from the collected clips based on simple tabulation of the instances of agreement. Inter‐rater agreement was assessed with Fleiss's κ and Gwet's agreement coefficient (AC). Results: Except in the case of two assessment items ("edematous change" and "easy bleeding"), κ or AC significantly exceeded 0.5 and the typical videos were judged to be applicable. For the two remaining items, the evaluation was repeated after clarifying the definitions of positive and negative findings. Eventually, they were recognized as typical. The completed video clip library contains 31 clips and is divided into five categories (http://www.jshbps.jp/modules/project/index.php?content_id=13 ). Conclusions: This clip library may be highly useful in clinical settings as a more objective standard for assessing surgical difficulty in LC. Abstract : To explore best practices for acute cholecystitis, multiple evaluators assembled a video clip library for 25 intraoperative findings associated with surgical difficulty in laparoscopic cholecystectomy. Kurata and colleagues describe the development of the library, which contains 31 clips in five categories and is accessible on the Japanese Society of Hepato‐Biliary‐Pancreatic Surgery website.